Native-plant amendments and topsoil addition enhance soil function in post-mining arid grasslands - Kneller, T.; Harris, Richard; Bateman, A.; Muñoz-Rojas, M. (Elsevier, 2018)
One of the most critical challenges faced in restoration of disturbed arid lands is the limited availability of topsoil. In post-mining restoration, alternative soil substrates such as mine waste could be an adequate growth media to alleviate the topsoil deficit, but these materials often lack appropriate soil characteristics to support the development and survival of seedlings. Thus, addition of exogenous organic matter may be essential to enhance plant survival and soil function. Here, we present a case study in the arid Pilbara region (north-west Western Australia), a resource-rich area subject to intensive mining activities. The main objective of our study was to assess the effects of different restoration techniques such as soil reconstruction by blending available soil materials, sowing different compositions of plant species, and addition of a locally abundant native soil organic amendment (Triodia pungens biomass) on: (i) seedling recruitment and growth of Triodia wiseana, a dominant grass in Australian arid ecosystems, and (ii) soil chemical, physical, and biological characteristics of reconstructed soils, including microbial activity, total organic C, total N, and C and N mineralisation. The study was conducted in a 12-month multifactorial microcosms setting in a controlled environment. Our results showed that the amendment increased C and N contents of re-made soils, but these values were still lower than those obtained in the topsoil. High microbial activity and C mineralisation rates were found in the amended waste that contrasted the low N mineralisation but this did not translate into improved emergence or survival of T. wiseana. These results suggest a short- or medium-term soil N immobilisation caused by negative priming effect of fresh un-composted amendment on microbial communities. We found similar growth and survival rates of T. wiseana in topsoil and a blend of topsoil and waste (50:50) which highlights the importance of topsoil, even in a reduced amount, for plant establishment in arid land restoration.